Upaya Preventif Kantor Urusan Agama (KUA) Dalam Mencegah Perceraian Masyarakat Waru Pamekasan - Hasan, Moh.; Imamah, Nur; Baidowi, Ach. (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2022)
Preventive efforts are efforts made by a person or agency in fixing existing problems through a prsikis approach. The purpose of this study was to describe the efforts of the Waru Pamekasan Religious Affairs Office before and during the divorce process to prevent divorce. The research was conducted qualitatively through a case study approach. Data collection techniques with interviews, documentation and observation. The validity of the data by triangulation techniques and sources. The results showed: (1) The efforts of the Waru Pamekasan Religious Affairs Office before the divorce process took place, namely: first with premarital guidance to prevent problems in the household. Second, with guidance after the marriage contract by giving advice or spiritual showers about marriage. Third, with the guidance of the Sakinah family. (2) The efforts of the Waru Pamekasan Religious Affairs Office at the time of the divorce process are: first, to approach the husband and wife in a family manner. Second, give advice to prevent divorce. Third, providing guidance, both individually and in groups through conversations to reveal the problems faced.